Study of The Effect of Supply Chain Integration Level on Operational Performance and the Moderating Role of Environmental Uncertainty: An Applied Study in Manufacturing Companies at King Abdullah II Ibn Al-Hussein Industrial City - Abu Zaid, "Mohammad Khair" (Jordan Journal of Business Administration, 2015)
The purpose of this research was to examine the impact of supply chain integration level on operational performance based on organizational capabilities and extended-resource-based-view. Furthermore, this research empirically investigated the moderating role of environmental uncertainty from contingency theory perspective. Data was collected through self–administrated questionnaire that was distributed among manufacturing companies in King Abdullah II Ibn Al-Hussein Industrial City. Total of (158) questionnaires were valid for analysis. Simple regression and Chow tests were used to analyze the collected data. Several significant findings were outlined in this research as follows: • There is an effect of internal integration, internal integration with the supplier, internal integration with the customer and total integration on operational performance. Results confirmed that the expansion of integration from internal to external increases the operational performance. • Both supply and technology uncertainty moderate the effect of supply chain integration level on operational performance. However, demand uncertainty does not moderate such effect. Based on these findings, several recommendations were developed. The most significant of these recommendations are to deploy information and communication technology (ICT) in the internal and external of organizations and enhance the relationship quality among the supply chain members.